Strengthening Certification of Graduate Prodi DIII Medical Record and Health Information as a Supporter in the Work of Medical Record Unit at Central Java Hospital - Edy Susanto; Elise Garmelia; Andhani Windari; Isnaini Qoriatul Fadhilah (Wealth Community Empowerment, 2024)
The problem faced by the hospital is one of the medical record units where in the recruitment process of PMIK officers who have not seen candidates who have certified specialized expertise in Casemix-based Health Care System Management is a value. The results of the study showed that the Head of Medical Record Installation has not given priority to graduates who have Casemix-based Healthcare System Management Certification in the financing claims section. The results of this dedication to the community are expected to be able to raise awareness among PMIK professional organizations about the importance of a PMIK to have a specialized training certificate of integrity in Casemix-based Healthcare Service System Management when performing tasks in a medical record unit. There is socialization and education in the media about the importance of the certification of integrity of specialized training on Casemix-based Health Care System Management in carrying out tasks in the medical record unit.